2016
DOI: 10.3928/01477447-20160517-05
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Distal Radius Fractures Treated by Volar Locking Plate Fixation

Abstract: The current study investigated the incidence of complications after surgery for distal radial fractures. This multicenter retrospective study was conducted at 11 institutions. A total of 824 patients who had distal radius fractures that were treated surgically between January 2010 and August 2012 were identified. The study patients were older than 18 years and were observed for at least 12 weeks after surgery for distal radius fractures with a volar locking plate. Sex, age, fracture type according to AO classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Although volar plating is the most popular surgical modality [9], complications, such as carpal tunnel syndrome and rupture of tendon(s), are often reported [10]. Thus, research continues for alternative surgical modalities to volar plating, such as the notional one (injectable bioresorbable polymer fixator) presented in the present work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although volar plating is the most popular surgical modality [9], complications, such as carpal tunnel syndrome and rupture of tendon(s), are often reported [10]. Thus, research continues for alternative surgical modalities to volar plating, such as the notional one (injectable bioresorbable polymer fixator) presented in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some have referred to this system as becoming "the treatment of choice" in cases where surgical treatment is deemed appropriate [9]. However, complications after fixation with this system, such as rupture of tendon(s), and its shortcomings, such as delay in wound healing, are well known [10]. Thus, there is scope for development of a new generation of innovative modalities as an alternative to the volar locking plate system.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a number of volar plate options exist, including fixed-angle and variable-angle locking plates, with their own potential complication profiles: Rates of nerve complications range from 0.4-14%, with CTS being the most commonly reported type. (38,48,51,74,94,99,102,103) One large multi-institutional retrospective study by Satake et al identified 694 patients treated by volar locking plate, of which only 4 cases of tendon rupture (0.6%) were reported, while 18 cases of CTS (2.6%) and 3 cases of CRPS (0.4%) were reported, indicating a greater incidence of nerve complications than tendon complications. (93) Reported rates of hardware-related complications range from 0-7%, with malunion being the most frequent.…”
Section: Volar Plate Specific Complicationsmentioning
confidence: 99%
“…(93) Reported rates of hardware-related complications range from 0-7%, with malunion being the most frequent. (38,48,51,74,94,99,102,103) Some studies have also directly compared the outcomes of volar non-locking and volar locking plates. One study by Obert et al retrospectively compared 31 patients treated by volar plating with non-locking screws to 121 patients treated by volar plating with locking screws and found no significant difference in the overall complication rates of the two groups (16.1% vs.…”
Section: Volar Plate Specific Complicationsmentioning
confidence: 99%
“…Distal radius fractures remain one of the most common orthopedic injuries, accounting for 8-17% of all extremity fractures, and open reduction and internal fixation with a volar locking plate has become the gold standard treatment to correct them [1][2][3][4]. However, several complications associated with volar locking plates have also become better defined [2,5,6]. Flexor pollicis longus (FPL) tendon rupture is one of the major complications, having an incidence rate of 0.2-12% [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%